Handbook of Fruit Wastes and By-Products: Chemistry, Processing Technology, and Utilization - Muzaffar, Khalid; Sofi, Sajad Ahmad; Mir, Shabir Ahmad (CRC Press, 2023)
Handbook of Fruit Wastes and By-Products: Chemistry, Processing Technology, and Utilization addresses the chemistry and valorization of wastes and by-products generated during the processing of fruits. It provides an overview of the recovery of bio-functional components from fruit processing residues and their utilization. Besides, this book is a valuable resource for scientists, researchers, professionals, and enterprises that aspire in the management of fruit processing wastes and by-products, and their utilization. Key features Provides comprehensive information about the chemistry of wastes and by-products obtained during fruit processing Provides in-depth information about the bioactive potential of fruit processing wastes and by-products Explores new strategies used for the proper valorization of fruit processing residues Describes the utilization of nutraceutical components derived from fruit processing residues in the fabrication of novel functional foods